Neck pain. Issue 10 (October 2015) - Lowe, Adam
Neck pain is a common musculoskeletal presentation in primary care; it can be due to a number of aetiologies. It may present as a prolonged history or secondary to a recent acute event. Neck pain that persists for less than 6 weeks is termed as acute and, in general, is thought to carry a favourable prognosis. Sub-acute is used to describe cases where neck pain persists from 6 weeks to 6 months. For durations greater than 6 months, neck pain tends to be classified as chronic. Careful history and clinical examination in primary care can differentiate the small number of patients with potential red flag symptoms from non-specific aetiologies. This may be a difficult task, and requires skill in ascertaining an accurate history and examination. In the majority of cases non-specific neck pain is the likely diagnosis, however, alternative significant causes should be considered in each presenting case. This article is aimed mainly at initial assessment in primary care and when to consider onward referral. The assessment and overall management is a similar approach to that used with regards to low back pain. Neck pain is overall less prevalent in comparison; however, serious pathology must be excluded in each case. It tends to be more prevalent in women. A significant percentage of patients who recover from neck pain will relapse. As a result early input management and education in patients presenting with neck pain can be a vital intervention.